Digital Estuaries: Exploring the Pedagogical Benefits of Virtual Reality Media in Geography and Spatial Analysis - Khoirul Habibah; Alfyananda Kurnia Putra; Sofie Nilsson; Christian Vielhaber (Universitas Negeri Gorontalo, 2023)
Learning eco-spatial concepts and estuary conservation concepts in Geography is often constrained by irrelevant learning media and limited field trips. As marine conservation is critical to addressing damage to coastal and marine ecosystems, there is an urgent need for innovative learning media that can bridge this gap. To address this, our research focuses on the development and evaluation of Virtual Reality Estuary learning media. This interactive tool provides a realistic virtual representation of the real world through a 360° panorama. It is designed to offer students an immersive experience, enhancing their understanding of the topics of eco-spatial concept and estuary conservation. We used a Research and Development approach using the Successive Approximations Model research method. This research uses primary and secondary data. Primary data is based on field data and product validation tests. Secondary data was obtained from literacy data from accredited journals. Data needs analysis using a questionnaire submitted to students. The analysis shows that the use of virtual reality media is needed in estuary learning. This research resulted in the development of Virtual Reality Estuary media. Virtual Reality Estuary media development products have gone through the media product validation test stage and material validation test with declared valid and feasible to use. So that students can do digital exploration through Virtual Reality Estuary in geography learning.